1996
DOI: 10.1203/00006450-199602000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Activity in Preterm Infants with Respiratory Distress Syndrome: Relationship to the Development of Bronchopulmonary Dysplasia

Abstract: Respiratory distress syndrome (RDS) is characterized by the presence of fibrin-rich exudates in the alveoli. Fibrin and its degradation products may play an important role in the pathogenesis of bronchopulmonary dysplasia (BPD). The purpose of this study was to test the hypothesis that preterm neonates with RDS have depressed alveolar fibrinolytic activity and that those with RDS progressing to BPD have an even greater impairment in alveolar fibrinolysis. Serial tracheal aspirate (TA) samples from intubated ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
1
17
1
Order By: Relevance
“…Conversely, uPA, being present essentially within the alveolar compartment, may not be crucial until alveolar leakage and subsequent fibrin deposition is present, after 72 h of hyperoxia. Several authors have reported that decreased fibrinolytic activity associated with experimental and clinical pulmonary lesions is a good predictive marker for the subsequent development of fibrosis (28,34,35). In accordance with this, it has been shown recently that PAI-1-mediated inhibition of fibrinolysis influences the severity of bleomycin-induced chronic lung fibrosis (36).…”
Section: Discussionsupporting
confidence: 51%
“…Conversely, uPA, being present essentially within the alveolar compartment, may not be crucial until alveolar leakage and subsequent fibrin deposition is present, after 72 h of hyperoxia. Several authors have reported that decreased fibrinolytic activity associated with experimental and clinical pulmonary lesions is a good predictive marker for the subsequent development of fibrosis (28,34,35). In accordance with this, it has been shown recently that PAI-1-mediated inhibition of fibrinolysis influences the severity of bleomycin-induced chronic lung fibrosis (36).…”
Section: Discussionsupporting
confidence: 51%
“…We know fibrin deposits are found within the lung's intravascular, interstitial and intra-alveolar spaces in RDS (12). It is also known that platelets play an important role in inflammation.…”
Section: Activated Inflammation and Clotting In Rdsmentioning
confidence: 99%
“…As is known from histopathologic studies, fibrin is a major part of hyaline membranes and therefore hyaline membranes can be regarded as locally produced clots in RDS (12,13). Schmidt described that intravascular thrombin-antithrombin III complex formation was related to disease severity in RDS (14).…”
mentioning
confidence: 99%
“…Aspirates were collected during routine tracheal suctioning of mechanically ventilated newborns (15). Infants were positioned in a supine posture with head midline.…”
Section: Tracheal Aspirate Collectionmentioning
confidence: 99%